2017
DOI: 10.1002/jmr.2692
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting and analyzing key residues in protein‐DNA complexes

Abstract: Protein-DNA interactions are involved in various fundamental biological processes such as replication, transcription, DNA repair, and gene regulation. To understand the interaction in protein-DNA complexes, the integrative study of binding and stabilizing residues is important. In the present study, we have identified key residues that play a dual role in both binding and stability from a nonredundant dataset of 319 protein-DNA complexes. We observed that key residues are identified in very less number of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 65 publications
(155 reference statements)
0
3
0
Order By: Relevance
“…For example, a 20-residue segment in the Fos-Jun complex has seven Arg residues, and six of them are in contact with DNA (Fig 4E; PDB ID: 1A02). It is well known that these residues are enriched for polynucleotide-binding interfaces [25,26]. Zhang et al reported a review for structural bioinformatics studies and their analyses of amino acid propensities for interactions; this concluded that positively charged residues are favored for polynucleotide interactions [25].…”
Section: Resultsmentioning
confidence: 99%
“…For example, a 20-residue segment in the Fos-Jun complex has seven Arg residues, and six of them are in contact with DNA (Fig 4E; PDB ID: 1A02). It is well known that these residues are enriched for polynucleotide-binding interfaces [25,26]. Zhang et al reported a review for structural bioinformatics studies and their analyses of amino acid propensities for interactions; this concluded that positively charged residues are favored for polynucleotide interactions [25].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, based on the rule of the Nucleic Acid Database (NDB) 26 , the protein-DNA complexes are divided into three categories: I) complexes with single-stranded DNA (SS), II) complexes with duplex DNA, III) miscellaneous complexes (MISC). According to previous studies 29,30 , it has been confirmed that protein-DNA binding site residues have an essential influence on the interaction of protein and DNA. Actually, the binding site residues are believed to play essential roles in directing the binding affinity.…”
Section: Classification Of Complexesmentioning
confidence: 85%
“…Motivation and Aim: DNA-protein interactions play a central role in such cellular processes as DNA replication, transcription, and repair [1]. Prediction of the interactions between DNA and protein is a significant but not trivial task [2].…”
mentioning
confidence: 99%